Administração na Capitania de São José do Rio Negro: líderes governamentais na estrutura social, política e poder no contexto amazônico português ocidental (1755 – 1798) - Lima, Evelen Araujo de (Brasil, 2024)
The project aims to analyze the profile and political activities of the military officers who served in the Captaincy of São José do Rio Negro between 1755 and 1798. The research will be centered on the governors in the Captaincy. With the hypothesis that the experience in the region influenced the selection of officers, as well as internal conflicts among colonial agents (especially concerning the implementation of indigenous and indigenist policies) and border conflicts. Primary sources will include the officers' ranks and consultations from the Concelho Ultramarino, alongside various printed documents.